The Influence of Service Quality on Customer Satisfaction Through Complaint Handling at the Regional Public Company for Domestic Wastewater Management in Banjarmasin City (PERUMDA PALD) - Muhammad Jihan Firdaus; Fanlia Prima Jaya (PT. Hanken SUkses Jaya, 2023)
The aim of this research is to determine the influence of Service Quality on Customer Satisfaction through Complaint Handling at the Regional Public Company for Domestic Wastewater Management in Banjarmasin City (PERUMDA PALD), both partially and simultaneously. This research employs a quantitative descriptive method. The population for this study consists of customers of the Regional Public Company for Domestic Wastewater Management in Banjarmasin City (PERUMDA PALD), totaling 5,924. The research sample is determined using the Slovin formula, resulting in a sample size of 100 respondents who will be surveyed using questionnaires. The data analysis technique employed is linear regression, and the software used for analysis is IBM SPSS Statistics version 25.0 x46. The findings of this research indicate that (1) partially, Service Quality significantly influences Complaint Handling, (2) partially, Service Quality significantly influences Customer Satisfaction, and (3) simultaneously, Service Quality and Complaint Handling, as intervening variables, significantly influence Customer Satisfaction.